Cytocompatible chitosan based multi-network hydrogels with antimicrobial, cell anti-adhesive and mechanical properties. (15th December 2018) - Zou, Wanjing; Chen, Yuxiang; Zhang, Xingcai; Li, Jianna; Sun, Leming; Gui, Zifan; Du, Bing; Chen, Shiguo
Highlights: Highly strength hydrogels were prepared based on natural polysaccharide chitosan. Chitosan can endow multi-network hydrogels with good antimicrobial activity. Multi-network hydrogels exhibit good cytocompatible and cell anti-adhesive properties. The compressive and tensile strength of hydrogels could be facilely tailored. The antimicrobial, cytocompatible, cell anti-adhesive property can be facilely tailored. Abstract: Hydrogel with good mechanical and biological properties has great potential and promise for biomedical applications. Here we fabricated a series of novel cytocompatible chitosan (CS) based double-network (DN) and triple-network (TN) hydrogels by physically-chemically crosslinking methods. Natural polysaccharide CS with abundant resources was chosen as the first network due to its good antimicrobial activity, biocompatibility and easy cross-linking reaction. Zwitterionic sulfopropylbetaine (PDMAPS) was chosen as the second network due its good biocompatibility, antimicrobial and antifouling properties. And nonionic poly(2-hydroxyethyl acrylate) (PHEA) was chosen as the final network due to its good biocompatibility, excellent nonfouling and mechanical properties. Cross-section SEM images showed that both CS/PHEA (DN1, the molar ratio of glutaraldehyde to structural unit of CS is 0.2/3.0) and CS/PDMAPS/PHEA (TN1, the molar ratio of glutaraldehyde to structural unit of CS is 0.2/3.0) hydrogels exhibited a smooth and uniformly dispersed porous microstructures with pore size distribution in the range of 20∼100 μm. The largest compressive stress and tensile stress of DN1 hydrogels reached 84.7 MPa and 292 kPa, respectively, and largest compressive stress and tensile stress of TN1 hydrogels could reach 81.9 MPa and 384 kPa, respectively. Moreover, the value of failure strain for TN1 gels reached 1020%. Besides excellent mechanical properties, DN1 and TN1 gels exhibited good antimicrobial, cytocompatible and antifouling properties due to introduction of antimicrobial chitosan, cell anti-adhesive PDMAPS and PHEA. The combination of the excellent mechanical and biological properties of multiple network hydrogels can provide a potential pathway to develop biomedical hydrogels as promising bioapplications in wound dressing and other biomedical applications.